Binding of PLD2-generated phosphatidic acid to KIF5B promotes MT1-MMP surface trafficking and lung metastasis of mouse breast cancer cells - Wang, Ziqing (Dev Cell, 2017)
Little is known about the cellular events promoting metastasis. We show that knockout of phospholipase D2 (PLD2), which generates the signaling lipid phosphatidic acid (PA), inhibits lung metastases in the mammary tumor virus (MMTV)-Neu transgenic mouse breast cancer model. PLD2 promotes local invasion through the regulation of the plasma membrane targeting of MT1-MMP and its associated invadopodia. A liposome pulldown screen identifies KIF5B, the heavy chain of the motor protein kinesin-1, as a new PA-binding protein. In vitro assays reveal that PA specifically and directly binds to the C-terminus of KIF5B. The binding between PLD2-generated PA and KIF5B is required for the vesicular association of KIF5B, surface localization of MT1-MMP, invadopodia, and invasion, in cancer cells. Taken together, these results identify a role of PLD2-generated PA in the regulation of kinesin-1 motor functions and breast cancer metastasis, and suggest PLD2 as a potential therapeutic target for metastatic breast cancer.